Integrated Learning Strategy Through Film Analysis as an Effort to Improve Students' Reading Interest at SMP Negeri 1 Cigugur - Aziz, Nur; Suryana, Yana (Universitas Wijaya Kusuma Surabaya, 2024)
Improving students' reading interest is a crucial aspect that educational institutions must prioritize. Despite the prevalence of social media as a primary source of information for students, there is a tendency to overlook the importance of cultivating a reading culture. Purpose Research. This study explores strategies for enhancing students' reading interest through movie analysis assignments, focusing on a case study at SMP Negeri 1 Cigugur. Research Method: The research employs a qualitative descriptive method, utilizing data collection through observation, interviews, and literature review. The study identifies factors contributing to the decline in students' reading interest. It proposes strategies for improvement through movie analysis assignments, using SMP Negeri 1 Cigugur as a case study. Results. The reading interest of students at SMP Negeri 1 Cigugur is significantly low. To address this issue, teachers implement a double-learning instructional strategy. This involves a movie analysis session and reading books relevant to the movie's content. The integrated learning strategy through movie analysis positively impacts students' reading interests. Furthermore, this approach indirectly imparts lessons on cinematography to the students. Keywords: Film Analysis, Integrated Learning, Reading Interest, Strategy.